Supporting students’ mental health and social emotional learning through community engagement and collaboration - Appel, Hoa B.; Walsh, Elaine; Marsh, Tyson E.; Brown, Crystal (Educational Research, 2023)
Background There is a recognised need internationally to reduce depression and anxiety among adolescents. As a population particularly sensitive to the amount and quality of social interaction, challenges for young people became magnified during COVID-19, particularly for students from under-represented and marginalised communities across the globe.Purpose This paper reports on a study conducted in Washington State, USA, that sought, via an alliance with students, parents, educators and community leaders, to gain insight into students’ lived experiences during the pandemic. It aimed to better comprehend how experiences affected social emotional learning and use this understanding to explore ways of reducing students’ mental health concerns.Method We created a diverse consortium, drawn from six schools. It comprised 13 students, predominantly students of colour, across the age range 11–18 years. Also participating were five other stakeholders: parents, educators and community leaders. The consortium’s involvement in five online discussion sessions led to the collection of rich data, as participants shared perspectives on pandemic experiences and learning. Additionally, we administered a survey about group collaboration. Data were analysed thematically.Findings The formation of the consortium represented a significant outcome in itself, providing a meaningful way of gaining understanding of the mental health and social emotional concerns of the students, their families and the other collaborators. Another outcome was the opportunity for students and parents to be at the same table and voice concerns about remote learning, sharing views on how changes affected students’ learning and mental health.Conclusion The consortium allowed for all voices to be heard. This research highlights the need for more attention and resources to be directed towards students of colour, not only across schools within the research setting but also elsewhere internationally. The connection of students with educators, parents and community stakeholders, by means of a consortium, can build a foundation through which the mental health needs of students in school may be addressed in future research.
Keywords: COVID-19; Social emotional learning; mental health; remote learning; students of colour; wellbeing